To Teach the University is to Teach Reparations: A Class Project - Conley, John (Radical Teacher, 2021)
If scholars and activists have long noticed that discussions about reparations re-emerge during periods of intense racial strife, then perhaps it is not surprising that reparations have again become an increasingly mainstream conversation in the US. Significantly, the university has not been insulated from these discussions, but in fact has become an important site of this struggle. As of now, most critical attention both on the page and in the streets has been pointed at private, elite universities in which the fact of the university’s founding during the antebellum US becomes a flash point for the discussions of the legacy of slavery. However, using my own university teaching context as an example, I show that the discussion of reparations in the context of the American University need not – and indeed, as many scholars and activists argue, should not – be limited to those institutions that were funded from slavery’s profits or were literally built with slave labor. By discussing a course project that looks into my own university’s history, I model one strategy for educators to normalize the discussion of reparations as well as expand its reach to encompass more recent and ongoing injuries to African-American communities.